Local agency costs of political centralization - Roger B. Myerson (Theoretical Economics, 2021)
We analyze a model of moral hazard in local public services which could be efficiently managed by officials under local democratic accountability, but not by officials who are appointed by the ruler of a centralized autocracy. The ruler might prefer to retain an official who diverted resources from public services but contributed part to benefit the ruler. The autocratic ruler would value better public services only when residents reduce taxable investments which become unprofitable without good public services. For local government to benefit local residents, they must have some decentralized power to punish an official who serves them badly even while serving the ruler well
Keywords: D72; H41; H70; 330; Local public goods; moral hazard; decentralized democracy; centralized autocracy